The Cleansing of the Temple : An Analysis of the Intention of Jesus - Lukito, Daniel Lucas (Stulos Theological Journal v. 1, no. 1, 1993)
Jesus’ cleansing of ihe Temple is probably one of his most puzzling actions reported in the Gospels. It is difficult to determine if Jesus went to Jerusalem with the intention of purifying the Temple, or whether he decided to do so only after he got there and saw what was going on. Also, it is hard to know with certainty whether there were one or two cleansings in Jesus’ ministry on earth, because the Synoptic Gospels recorded this event in the last days of Jesus’ ministry, whereas John put it in his early ministry in chapter two. This article particularly seeks to examine various interpretations that have been proposed in dealing with the questions of Jesus’ intention. But before that, we want to examine several difficult problems which are primarily connected or closely related to this event. So, after briefly reviewing some of the more important possibilities concerning our main subject, we will propose a case for what seems to be the most likely hypothesis. We admit in the concluding section that there are still some unresolved problems which emerge from this topic.
Keywords: Jesus Christ -- Cleansing of the Temple.